To Actively Initialize Active Learning. (November 2022) - Yang, Yazhou; Loog, Marco
Highlights: The initialization problem of active learning is addressed, which is how to find a set of labeled samples which contains at least one instance per category. A new active initialization criterion, the Nearest Neighbor Criterion, is proposed for the initialization task. The impacts of different initialization strategies on the whole active learning process are further investigated. Excellent performance of the proposed method in comparison with state-of-the-art approaches is demonstrated. Abstract: Though much effort has been spent on designing new active learning algorithms, little attention has been paid to the initialization problem of active learning, i.e., how to find a set of labeled samples which contains at least one instance per category. This work identifies the initialization of active learning as a separate and novel research problem, reviews existing methods that can be adapted to be used for this task and, in addition, proposes a new active initialization criterion: the Nearest Neighbor Criterion. Experiments on 16 benchmark datasets verify that the novel method often finds an initialization set with fewer queried samples than other methods do.